Universal gravity-driven isothermal turbulence cascade in disk galaxies - Fensch, Jérémy; Bournaud, Frédéric; Brucy, Noé; Dubois, Yohan; Hennebelle, Patrick; Rosdahl, Joakim (Astronomy and astrophysics, 2023)
While interstellar gas is known to be supersonically turbulent, the injection processes of this turbulence are still unclear. Many studies suggest a dominant role of gravitational instabilities. However, their effect on galaxy morphology and large-scale dynamics varies across cosmic times, in particular, due to the evolution of the gas fraction of galaxies. In this paper, we propose numerical simulations to follow the isothermal turbulent cascade of purely gravitationally driven turbulence from its injection scale down to 0.095 pc for a gas-poor spiral disk and a gas-rich clumpy disk. For this purpose, and to lift the memory-footprint technical lock of sufficiently resolving the interstellar medium of a galaxy, we developed an encapsulated zoom method that allows us to self-consistently probe the self-generated turbulence cascade over three orders of magnitude on spatial scales. We followed this cascade for 10 Myr. We find that the turbulent cascade follows the same scaling laws in both setups. Namely, in both cases, the turbulence is close to equipartition between its compressive and solenoidal modes, the velocity power spectrum follows the Burgers scaling, and the density power spectrum is rather shallow, with a power-law slope of −0.7. Last, gravitationally bound substructures follow a mass distribution with a −1.8 slope, similar to that of CO clumps. These simulations thus suggest that gravity-driven isothermal turbulent cascades are universal in disk galaxies across cosmic time.
Gesehen am 05.07.2023